Poetic Licence for Major Arab scholars until the End of the Fourth Century(AH) - Sami Awad (دراسات فی اللغه العربیه و آدابها)
Â Â  This Study deals with the issue of poetic licence.This issue remained vogue until the advent of Al-Khaleel Bin Ahmad Al-Faraheedi,who established the basis of this concept depending on his deep awareness of the differences between the poetic language and ordinary speech .To understand what he did we need to first explain AL-Kaleels views on poetic licence. Â  Moreover Ø the Study explicatesthe concept of poetic licence according to Sibaweih in his book Ø Al-Kitab Ø and then sheds light on the difference among ancient and modern researchers. this Study also discusses Ibn Jenni's significant ideasregarding poetic licence . Finally, the relevant ideas about poetic licence by AL-Sarraj and his disciple,Abu said AL-Sirafi,Ibn fares and Abi Hilal AL-Askari discussed.It is worth noting that this article does not have enough space to present the ideas by all the scholars before the 4 th century (AH)